Vaccination with the Surface Proteins MUL_2232 and MUL_3720 of Mycobacterium ulcerans Induces Antibodies but Fails to Provide Protection against Buruli Ulcer. - Miriam Bolz; Angèle Bénard; Anita M Dreyer; Sarah Kerber; Andrea Vettiger; Wulf Oehlmann; Mahavir Singh; Malcolm S Duthie; Gerd Pluschke (Public Library of Science (PLoS), 2016)
BACKGROUND:Buruli ulcer, caused by infection with Mycobacterium ulcerans, is a chronic ulcerative neglected tropical disease of the skin and subcutaneous tissue that is most prevalent in West African countries. M. ulcerans produces a cytotoxic macrolide exotoxin called mycolactone, which causes extensive necrosis of infected subcutaneous tissue and the development of characteristic ulcerative lesions with undermined edges. While cellular immune responses are expected to play a key role against early intracellular stages of M. ulcerans in macrophages, antibody mediated protection might be of major relevance against advanced stages, where bacilli are predominantly found as extracellular clusters. METHODOLOGY/PRINCIPAL FINDINGS:To assess whether vaccine induced antibodies against surface antigens of M. ulcerans can protect against Buruli ulcer we formulated two surface vaccine candidate antigens, MUL_2232 and MUL_3720, as recombinant proteins with the synthetic Toll-like receptor 4 agonist glucopyranosyl lipid adjuvant-stable emulsion. The candidate vaccines elicited strong antibody responses without a strong bias towards a TH1 type cellular response, as indicated by the IgG2a to IgG1 ratio. Despite the cross-reactivity of the induced antibodies with the native antigens, no significant protection was observed against progression of an experimental M. ulcerans infection in a mouse footpad challenge model. CONCLUSIONS:Even though vaccine-induced antibodies have the potential to opsonise the extracellular bacilli they do not have a protective effect since infiltrating phagocytes might be killed by mycolactone before reaching the bacteria, as indicated by lack of viable infiltrates in the necrotic infection foci.